Friction Stir Welding of Dissimilar AA7075-T6 to AZ31B-H24 Alloys. (12th December 2017) - Hernández-García, D.; Saldaña-Garcés, R.; García-Vázquez, F.; Gutiérrez-Castañeda, E.J.; Deaquino-Lara, R.; Verdera, D.
Abstract: In the present investigation, AA7075-T6 alloys and AZ31B-H24 were joined by the FSW process using the following range of parameters: rotational speed between 200 and 800 rpm, welding speed from 30 to 60 mm/min and a tilt angle from 1° to 3°. In some cases, a tool offset of 1 mm was used into Mg-based alloy. The experimental results show that sound and good joints can be obtained by positioning the tool in the middle of the joint-line using a rotational speed of 200 rpm, a welding speed of 30 mm/min and a tool tilt angle of 1°. The hardness and ultimate tensile strength in the stir zone were 122 Hv and 61.35 MPa, respectively. Also, it is important to mention that the Al3 Mg2 and Al12 Mg17 intermetallics compounds were observed in the this zone besides some defects like cavities and tunnel.